Implementasi Konseling Realitas dalam Menangani Krisis Identitas pada Remaja - Padillah, Raup (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2020)
Adolescence is a time when the child is growing to the stage of becoming an adult that can not be determined with certainty. A individual who can happily go through puberty will become a personable adult, and vice versa. This is decided throughout the process of establishing an individual's identity. In the field of developmental psychology, identity forming is the key role in the growth of personality, and is supposed to be completed at the end of adolescence. Many teens have an identity crisis because they have trouble understanding who they really are, so they need to be helped by real-life therapy. The definition of truth therapy is considered suitable for coping with the issue of the adolescent identity crisis. The protocols for the phases of the research carried out include: problem recognition, data collection, therapy, evaluation and follow-up. Based on the outcomes of reality therapy, it can be seen that the teenager is very closed in discovering himself so that he can not make choices on his own, can not manage to prevent confrontation with others, can not accept different expressions of feelings for himself and others. Like the rest. The noticeable effect of reality therapy care is that they lack trust in their abilities and do not appear to be self-understood.